Ujaran Penolakan dalam Bahasa Jepang dan Bahasa Bali - Putri, Ni Made Mia Septiarini; Indra Pradhana, Ngurah; Rauh Artana, I Nyoman (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2020)
The study, entitled "Refusal  in Japanese and Balinese" aims to find out the refusal strategies in Japanese and Balinese contained in Japanese novels Narataaju and Balinese novels Sentana.The theory used in this study is the theory of Refusal Strategy according to Beebe et al. (1990) and Theory of Determination of Politeness Factors according to Mizutani and Mizutani (1987). This research uses descriptive analysis method in presenting data.The analysis shows that in Narataaju's novel there are three strategies of refusal. Three data with direct refusal strategy, five data with indirect refusal strategy, and two data with mixed refusal strategy. Factors influencing refusal in Japanese are social relations and intimacy. There are six forms of rejection strategies in Japanese. In the Balinese novel Sentana there are also three strategies of refusal. Two data with direct refusal strategy, four data with indirect refusal strategy and two data with mixed refusal strategy. Factors influencing refusal in Balinese are situation, social status, and age. From the results of the study found two similarities and one difference in the refusal in Japanese and Balinese. Keyword: refusal, strategy, factor